Caring for the Common Home and Calling for a Diverse Future: Pope Francis and Byung-Chul Han in Dialogue - Martins, Adriana Alves de Paula (Religions, 2023)
The first few decades of the twenty-first century have posed various challenges to humankind such as the worldwide impact of the changing patterns of globalization processes, economic crises, the pandemic, the war in Ukraine, and the specter of deglobalization illustrate. The unknown and unpredictable future is a reason for utmost concern for the contemporary society that Byung-Chul Han characterizes as an “achievement society”—one that is dominated by “excessive positivity” and that has evolved into a “doping society”. This “palliative society” is such because it is unable to cope with pain, and it is marked by a kind of permanent analgesia that prevents urgent reforms from taking place. In this essay, I examine how Pope Francis’s encyclical letters Laudato Si’ (2015) and Fratelli Tutti (2020)—by calling for an integral ecology (which connects environmental, economic, political, social, cultural, and ethical issues), social friendship, solidarity, and the common good—instill hope in the burnout society that Han reflects upon, urges action toward, and encourages changes to overcome in the current environmental and human crisis, as well as to building a diverse future that is not palliative.